2007
DOI: 10.1162/rest.89.2.343
|View full text |Cite
|
Sign up to set email alerts
|

Growth Controls, Real Options, and Land Development

Abstract: Many urban growth controls attempt to check sprawl by restricting allowable new housing densities. However, land may be undeveloped to preserve its real-option value. Real options in land markets arise from uncertainty as to the optimum use of a site. By limiting allowable development choices, growth controls can narrow real options and potentially accelerate investment. This paper examines the effect of price volatility, a generator of option value, on the timing of development after the imposition of an Urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 42 publications
(41 reference statements)
3
69
0
1
Order By: Relevance
“…In a study on UGBs in Seattle by Cunningham, a pseudo-UGB was constructed for Seattle's UGB to test the probability of land development, both within and outside the UGB [55]. This article refers to this practice, and we obtained a new narrow greenbelt by indenting it 500 m from the inner and outer boundaries of the present greenbelt.…”
Section: Robustness Checksmentioning
confidence: 99%
“…In a study on UGBs in Seattle by Cunningham, a pseudo-UGB was constructed for Seattle's UGB to test the probability of land development, both within and outside the UGB [55]. This article refers to this practice, and we obtained a new narrow greenbelt by indenting it 500 m from the inner and outer boundaries of the present greenbelt.…”
Section: Robustness Checksmentioning
confidence: 99%
“…Subsequent amendments to the Land Acquisition Act changed the statutory date for purposes of valuation for compensation to 1 January of 1986, 1992, and 1995. In 2007, the use of a historical statutory date was removed by Parliament, and compensation has since been pegged to full market value.…”
Section: The Land Acquisition Act 1966mentioning
confidence: 99%
“…However, in the case of Singapore, these lower development intensity effects do not exist for land leases sold by the government because the government defines the land use, development intensity (plot ratio), and time-to-project completion under the Government Land Sales Programme. The detailed planning regulations basically strip away development options and reduce the uncertainty linked to the optimal time to exercise the real option of land development, thus accelerating investments (Cunningham 2007).…”
Section: Land Lease Systemmentioning
confidence: 99%
“…www.eea.europa.eu/data-and-maps/indicators/nationally-designated-protectedareas#tab-latest-figures-and-vizualizations. 4 Environment Canada -Canadian Protected Areas -Status Report 2006-2011 It has been shown that land-use regulations have strong influence on the supply of housing, and thus its price (Pollakowski and Wachter, 1990;Sommerville, 2000a and2000b;Raphael, 2004 andGlaeser and Ward, 2009;Kok et al, 2014), its location and pattern of development (Quigley and Swoboda, 2007;Ihlanfeldt, 2007;Cheshire and Vermeulen, 2009), the timing of development (Mayer and Sommerville, 2000a;Cunningham, 2007), and social segregation (Levine, 1999). Land-use regulations may also potentially have non-negligible distributional effects (Quigley and Swoboda, 2007;Cheshire and Vermeulen, 2009).…”
Section: Introductionmentioning
confidence: 99%